1999
DOI: 10.1146/annurev.biophys.28.1.129
|View full text |Cite
|
Sign up to set email alerts
|

NITROXIDE SPIN-SPIN INTERACTIONS: Applications to Protein Structure and Dynamics

Abstract: Measurement of the distance between two spin label probes in proteins permits the spatial orientation of elements of defined secondary structure. By using site-directed spin labeling, it is possible to determine multiple distance constraints and thereby build tertiary and quaternary structural models as well as measure the kinetics of structural changes. New analytical methods for determining interprobe distances and relative orientations for uniquely oriented spin labels have been developed using global analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
116
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(117 citation statements)
references
References 72 publications
0
116
0
1
Order By: Relevance
“…In particular, we have used the nitroxide scanning strategy in the middle section and the C-terminal region of the core complex. Because there are two copies of syntaxin 1A in the complex, single spin labeling on syntaxin 1A renders two nitroxide spin labels, and the distance between the pairs can be determined (26,27). From EPR studies we found that the middle section of the t-SNARE bundle is a coiled coil that is identical to that of the ternary complex.…”
mentioning
confidence: 93%
“…In particular, we have used the nitroxide scanning strategy in the middle section and the C-terminal region of the core complex. Because there are two copies of syntaxin 1A in the complex, single spin labeling on syntaxin 1A renders two nitroxide spin labels, and the distance between the pairs can be determined (26,27). From EPR studies we found that the middle section of the t-SNARE bundle is a coiled coil that is identical to that of the ternary complex.…”
mentioning
confidence: 93%
“…Exchange decays more rapidly with distance than does the dipolar interaction. Spectral simulation shows that isotropic exchange is negligible compared with dipolar interactions for unlike nitroxides with separations in the intermediate range: r 12 = 1.28À1.56 nm [13].…”
Section: Magnetic Dipole-dipole Interaction For Like and Unlike Spinsmentioning
confidence: 94%
“…For example, measurement of the distance between two spin labels in proteins permits distinguish the spatial orientation of elements of defined secondary structure (Hustedt & Beth, 1999). By using site-directed spin labeling, it is possible to determine multiple distance values and thereby build tertiary and quaternary structural models as well as measure the dynamics of structural changes.…”
Section: Nmmentioning
confidence: 99%
“…New methods have also been developed for determining interprobe distances for randomly oriented spin labels. These methods are being applied to a wide range of structural problems, including peptides, soluble proteins, and membrane proteins, that are not readily characterized by other structural techniques (Hustedt & Beth, 1999). Nevertheless, a simplemeasured d1/d parameter was used rather often during these years.…”
Section: Nmmentioning
confidence: 99%